2022
DOI: 10.1039/d1ta09750d
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of Co catalysts with atomically dispersed CoNx active sites on ammonia borane hydrolysis for hydrogen generation

Abstract: The development of low-cost, highly efficient and durable catalysts is the key to the practical use of ammonia borane as a promising storage material for on-board hydrogen production. Atomically dispersed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…As determined by XANES analysis in our previous results, Co/N-CNTs could present certain amounts of Co-SAs on the CNT, together with the Co NPs. 24…”
Section: Resultsmentioning
confidence: 99%
“…As determined by XANES analysis in our previous results, Co/N-CNTs could present certain amounts of Co-SAs on the CNT, together with the Co NPs. 24…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic performance of Pt@NiO/Ni-CNT was studied for hydrolysis of AB against the reference catalysts, and the Pt@NiO/Ni-CNT catalyst exhibited a high catalytic rate with B41. 112 reported Co NPs loaded on the CNT support with atomically dispersed CoN x active sites as low-cost, highly efficient and durable catalysts for AB hydrolysis (Fig. 6e).…”
Section: Carbonaceous Materialsmentioning
confidence: 94%
“…This work suggested that the engineering of the interfacial structure of bimetal catalysts plays an important role in improving synergistic catalytic performances. Poon et al 112 reported Co NPs loaded on the CNT support with atomically dispersed CoN x active sites as low-cost, highly efficient and durable catalysts for AB hydrolysis (Fig. 6e).…”
Section: Porous Materials Supported Metal Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, atomically dispersed metal-supported catalysts maximize the efficiency of metal utilization and act as a robust support for metal nanoparticles. 18 M-N-C (Fe, Co, and Ni) single-atom catalysts (SACs) with metals strongly linked to surrounding N atoms have shown promising performances in electrochemical 19 and thermochemical reactions. 20…”
Section: Introductionmentioning
confidence: 99%